2017
DOI: 10.2147/ott.s129502
|View full text |Cite
|
Sign up to set email alerts
|

Human omental adipose-derived mesenchymal stem cell-conditioned medium alters the proteomic profile of epithelial ovarian cancer cell lines in vitro

Abstract: Mesenchymal stem cells (MSCs) have been reported to participate in the formation of supportive tumor stroma. The abilities of proliferation and invasion of human epithelial ovarian cancer (EOC) cells were significantly enhanced when indirectly cocultured with human omental adipose-derived MSCs (O-ADSCs) in vitro. However, the underlying mechanisms remain poorly understood. In this study, EOC cells were cultured with conditioned medium (CM) from O-ADSCs (O-ADSC), and the effect of O-ADSC CM on the proteomic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…In addition, 100 μM of Cd treatment potentially reduced stemness of SKOV-3 cancer cells caused by TGF-beta. Matrix metalloproteinases (MMPs) including MMP-2, MMP-7, and MMP-9 are known to promote tumor progression and cancer stemness [ 21 ]. We found that TGF-beta treatment significantly increased the levels of MMP-2, MMP-7, and MMP-9 while Cd treatment decreased MMPs levels (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 100 μM of Cd treatment potentially reduced stemness of SKOV-3 cancer cells caused by TGF-beta. Matrix metalloproteinases (MMPs) including MMP-2, MMP-7, and MMP-9 are known to promote tumor progression and cancer stemness [ 21 ]. We found that TGF-beta treatment significantly increased the levels of MMP-2, MMP-7, and MMP-9 while Cd treatment decreased MMPs levels (Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Omental microenvironment serves as a major site for tumor metastases, proliferation, and chemotherapy response in EOC. It has now been shown that omentum acts via secretion of paracrine growth factors although the underlying mechanisms are not fully understood . Pathologic review of notable morphological differences in OASCs from the present study possibly reflected the effect that tumor cells have on omental microenvironment and in turn influenced their secretomic expression.…”
Section: Discussionmentioning
confidence: 99%
“…Both proliferation and invasion of human EOC cells are remarkably enhanced upon co-culture with omental adipose-derived MSCs (O-ADSCs) in vitro , and a recent study revealed a global increase in protein expression in the EOC cells treated with conditioned media (CM) from O-ADSC (Zhang et al, 2017 ). Specifically, nine proteins were identified with differential expression after CM treatment, which are linked to carcinogenesis, apoptosis and migration of cancer cells, suggest that O-ADSCs alter the proteomic profile of EOC cells via paracrine mechanism in favor of EOC progression (Zhang et al, 2017 ).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%